Food Education for a Healthy Lifestyle: A Study on Primary School Students in Remote Indigenous Communities in Central Sulawesi - Minarni Nontji; Lukman Nadjamuddin; Sahrul Saehana; Kasmudin Mustapa; Abdul Rahman; Muhammad Zaky; Widyastuti Widyastuti; Windayanti Windayanti (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to evaluate the effectiveness of a food education program in promoting healthy lifestyles among elementary school students in remote indigenous communities in Central Sulawesi. The research employed pre-test and post-test design, measuring various aspects before and after the intervention. The sample included students, teachers, staff, and parents. The results demonstrated significant improvements across multiple domains. Students' nutritional knowledge increased by 33.40 points, from 45.20% to 78.60%. Attitudes toward healthy food improved by 26.00 points, rising from 64.00% to 90.00%. Food consumption practices showed 38.00 points increase in vegetable and fruit intake, alongside a 60.40% reduction in unhealthy snacking. The percentage of students with normal Body Mass Index (BMI) rose by 14.00 points, from 68% to 82%. Physical activity levels also surged significantly by 41.70 points, from 50.00% to 91.70% of daily recommendations. The program exhibited strong sustainability potential, with 85.00% support from teachers and school staff, and a 70.00% increase in parental awareness. Community-level impacts included a 40.00% rise in demand for local vegetables and 65.00% of families starting home vegetable gardens. Students' cooking skills advanced, with 75.00% able to prepare traditional healthy foods and 60.00% sharing healthy recipes with their families. Nutritional literacy improved markedly, evidenced by a 45.00% increase in the ability to read food labels. In conclusion, this intervention successfully enhanced students' knowledge, attitudes, and practices in nutrition and health through food education, yielding positive impacts that foster healthy lifestyles among elementary school students in remote indigenous communities in Central Sulawesi